Moral enhancement and personal autonomy. - Venter, Lucas (My University, 2013)
In this thesis, I examine the extent to which moral enhancement, the biomedical alteration of an individual’s disposition to act according to good or bad motives, will in uence his capacity for selfgovernance. Following a discussion of the salient features of moral enhancement, a plausible list of conditions against which to measure the compatibility of moral enhancement with personal autonomy is expounded. e core elements of moral enhancement are weighed against these conditions in order to establish the ways in which these core elements are compatible with the conditions of personal autonomy. I argue that moral enhancement need not lead to a diminishment of personal autonomy, provided it serves merely as a mechanism to help an agent overcome the deterministic limitations that prevent him from bringing his lower-order desires into conformity with the higher-order desires that he has arrived at through independent, thoughtful deliberation.
Keywords: Ethics.; Autonomy (Philosophy).